Roles for NHERF1 and NHERF2 on the regulation of C3a receptor signaling in human mast cells. - Hariharan Subramanian (PLoS ONE, 2012)
The anaphylatoxin C3a binds to the G protein coupled receptor (GPCR, C3aR) and activates divergent signaling pathways to induce degranulation and cytokine production in human mast cells. Adapter proteins such as the Na(+)/H(+) exchange regulatory factor (NHERF1 and NHERF2) have been implicated in regulating functions of certain GPCRs by binding to the class I PDZ (PSD-95/Dlg/Zo1) motifs present on their cytoplasmic tails. Although C3aR possesses a class I PDZ motif, the possibility that it interacts with NHERF proteins to modulate signaling in human mast cells has not been determined.Using reverse transcription PCR and Western blotting, we found that NHERF1 and NHERF2 are expressed in human mast cell lines (HMC-1, LAD2) and CD34(+)-derived primary human mast cells. Surprisingly, however, C3aR did not associate with these adapter proteins. To assess the roles of NHERFs on signaling downstream of C3aR, we used lentiviral shRNA to stably knockdown the expression of these proteins in human mast cells. Silencing the expression of NHERF1 and NHERF2 had no effect on C3aR desensitization, agonist-induced receptor internalization, ERK/Akt phosphorylation or chemotaxis. However, loss of NHERF1 and NHERF2 resulted in significant inhibition of C3a-induced mast cell degranulation, NF-κB activation and chemokine production.This study demonstrates that although C3aR possesses a class I PDZ motif, it does not associate with NHERF1 and NHERF2. Surprisingly, these proteins provide stimulatory signals for C3a-induced degranulation, NF-κB activation and chemokine generation in human mast cells. These findings reveal a new level of complexity for the functional regulation of C3aR by NHERFs in human mast cells.